Measuring luteinising hormone pulsatility with a robotic aptamer-enabled electrochemical reader - Liang, Shaolin; Kinghorn, Andrew B.; Voliotis, Margaritis; Prague, Julia K.; Veldhuis, Johannes D.; Tsaneva-Atanasova, Krasimira; McArdle, Craig A.; Li, Raymond H. W.; Cass, Anthony E. G.; Dhillo, Waljit S.; Tanner, Julian A. (Nature communications, 2019)
Normal reproductive functioning is critically dependent on pulsatile secretion of luteinising hormone (LH). Assessment of LH pulsatility is important for the clinical diagnosis of reproductive disorders, but current methods are hampered by frequent blood sampling coupled to expensive serial immunochemical analysis. Here, we report the development and application of a Robotic APTamer-enabled Electrochemical Reader (RAPTER) electrochemical analysis system to determine LH pulsatility. Through selective evolution of ligands by exponential enrichment (SELEX), we identify DNA aptamers that bind specifically to LH and not to related hormones. The aptamers are integrated into electrochemical aptamer-based (E-AB) sensors on a robotic platform. E-AB enables rapid, sensitive and repeatable determination of LH concentration profiles. Bayesian Spectrum Analysis is applied to determine LH pulsatility in three distinct patient cohorts. This technology has the potential to transform the clinical care of patients with reproductive disorders and could be developed to allow real-time in vivo hormone monitoring. Assessment of luteinising hormone pulsatility is important in the diagnosis of reproductive disorders. Here the authors develop a DNA aptamer-based electrochemical analysis integrated into a robotic platform for high-throughput and sensitive analysis.